2011
DOI: 10.3109/0284186x.2010.543696
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as predictor of sunitinib treatment outcome in metastatic renal cell carcinoma

Abstract: Sunitinib-associated hypertension may be a strong predictive marker for treatment efficacy in metastatic RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 12 publications
6
49
1
1
Order By: Relevance
“…Rini et al [10] were the first to describe sunitinib-induced hypertension as a strong positive predictive value for PFS and OS in mRCC patients. Recently, Bono et al [17] found similar results in a retrospective trial of 64 consecutive mRCC patients treated with sunitinib. In this trial, 38% of patients developed hypertension during treatment with sunitinib and were found to have significant increases in overall response rate, PFS and OS in comparison to patients who did not develop hypertension.…”
Section: Discussionsupporting
confidence: 63%
“…Rini et al [10] were the first to describe sunitinib-induced hypertension as a strong positive predictive value for PFS and OS in mRCC patients. Recently, Bono et al [17] found similar results in a retrospective trial of 64 consecutive mRCC patients treated with sunitinib. In this trial, 38% of patients developed hypertension during treatment with sunitinib and were found to have significant increases in overall response rate, PFS and OS in comparison to patients who did not develop hypertension.…”
Section: Discussionsupporting
confidence: 63%
“…In study with sunitinib, Rini et al [5] demonstrated that patients with hypertension defined by maximum systolic BP ≥140 mm Hg had significantly longer survival parameters of both PFS and overall survival. Bono et al [4] showed that persistent BP >150/100 mm Hg or BP requiring intensification of preexisting antihypertensive medication are the positive predictive factors in patients treated with sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of sunitinib, this effect has already been thoroughly analyzed [3,4,5,6], and it has been shown that a significant risk of the development of heart failure exists during treatment with sunitinib. This risk may be associated with iatrogenic hypertension [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with hypertension continued to survive longer than patients without hypertension, independent of use of antihypertensive agents, sunitinib dose reductions, or both. Several other studies have supported this notion [6][7][8][9]. However, the definition of hypertension and methodology may impact results [10].…”
mentioning
confidence: 94%
“…Treatment-induced adverse events and their impact on outcome were assessed in patients with mRCC treated with sunitinib at various starting doses [12]. A milder definition for thrombocytopenia (<LLN) was used whereas definitions for hypertension and neutropenia were unchanged from previous studies [7,11]. The development during therapy of hypertension, neutropenia, and thrombocytopenia was associated significantly with longer PFS and OS.…”
mentioning
confidence: 99%